Cefiderocol-Based Regimen for Acinetobacter NDM-1 Outbreak - Giovanna Travi; Francesco Peracchi; Marco Merli; Noemi Lo Re; Elisa Matarazzo; Livia Tartaglione; Alessandra Bielli; Giorgia Casalicchio; Fulvio Crippa; Chiara S. Vismara; Massimo Puoti (MDPI AG, 2024)
Variable outcomes have been reported with cefiderocol in infections due to carbapenem-resistant Acinetobacter baumannii (CRAB). Nonetheless, it may be the only option for metallo-beta-lactamase-producing strains. We describe an outbreak of NDM-CRAB infections treated with cefiderocol. Thirty-eight patients were colonized and/or infected. Thirteen patients developed a systemic infection. A clinical cure was achieved in 10 (83%) patients, one VAP and 9 BSIs, at day 7. In vitro, the activity of cefiderocol does not appear to match in vivo effectiveness using currently available commercial tests. Despite high clinical cures, overall mortality remains high in severely ill patients. Cefiderocol may be considered in this specific setting, though the implementation of susceptibility tests and infection control measures is mandatory.